Electropolymerization and Electrochemical Pesticide Sensor Application of Metallophthalocyanines Bearing Polymerizable Morpholin Groups - ÖZKAYA, ALİ RIZA; KOCA, ATIF (ELECTROCHEMICAL SOC INC, 2016)
In this paper, new metallophthalocyanines (MPc) were synthesized by cyclotetramerization of 4-{[4-(2-morpholin-4-ylethoxy)benzyl]oxy}phthalonitrile. To increase potential application of MPcs, redox active Co(II), Mn(III) and Ti(IV)O metal centers were preferred. MPcs were decorated with redox active and electropolymerizable {[4-(2-morpholin-4-ylethoxy)benzyl]oxy} substituents in order to coat the complexes with electropolymerization. Synthesized MPcs were characterized with UV-Vis, IR, H-1-NMR, C-13-NMR and MS (ES+ and MALDI-TOF) spectroscopies and voltammetry and in situ spectroelectrochemistry techniques. Voltammetric and in situ spectroelectrochemical analyses indicated that all complexes gave metal based reduction processes in addition to the Pc based processes. During oxidation reaction, all complexes were coated on the glassy carbon electrode (GCE) surface with oxidative electropolymerization reactions. Redox active and conductive GCE/MPc electrodes were constructed with the electropolymerization of MPcs and these electrodes were tested as active pesticide sensors for eserine, parathion, diazinon and fenitrothion pesticides. CoPc did not interact with any pesticide compound while MnPc and TiOPc selectively sensed diazinon and eserine, respectively. (C) 2016 The Electrochemical Society. All rights reserved.
Keywords: MOLECULARLY IMPRINTED POLYMERS; GLASSY-CARBON ELECTRODE; COBALT PHTHALOCYANINE; MANGANESE PHTHALOCYANINE; ORGANOPHOSPHATE PESTICIDES; SPECTROELECTROCHEMICAL CHARACTERIZATION; SUBSTITUTED COBALT; NERVE AGENTS; THIN-FILMS; ACETYLCHOLINESTERASE